(untitled) - Smith, G. Stevenson (Chicago, 2002)
This book provides a step-by-step guide that focuses on accounting methods that fit the nonprofit world, such as responsibility accounting life cycle costing, and activity-based accounting as an alternative to traditional cost reporting. Each method is explained and illustrated within the nonprofit context. New to this edition are current cost estimates, new or updated figures on break-even analysis, lease alternatives, journal entries, and variable and fixed costs, and a quick-reference glossary that will help you "talk the talk." The only accounting book you'll need to get your books in tip-top shape, this edition provides library managers the tools and methods to: - Direct and monitor resources to communicate financial information - Control costs using long-term forecasting - Evaluate library services and boost performance - Make smart buying decisions
Keywords: Library finance,Libraries,Nonprofit organizations,Tài chính thư viện,Thư viện,Tổ chức phi lợi nhuận; Accounting,Accounting,Kế toán,Kế toán